Comparison of the numerical stability of methods for anharmonic calculations of vibrational molecular energies - Danecek, Petr; Bour, Petr (Journal of computational chemistry, 2007)
On model examples, we compare the performance of the vibrational self-consistent field, variational, and four perturbational schemes used for computations of vibrational energies of semi-rigid molecules, with emphasis on the numerical stability. Although the accuracy of the energies is primarily dependent on the quality of the potential energy surface, approximate approaches to the anharmonic vibrational problem often do not converge to the same results due to the approximations involved. For furan, the sensitivity to variations of the anharmonic potential was systematically investigated by adding random noise to the cubic and quartic constants. The self-consistent field methods proved to be the most resistant to the potential variations. The second order perturbational techniques are sensitive to random degeneracies and provided the least stable results. However, their stability could be significantly improved by a simple generalization of the perturbational formula. The variational configuration interaction is practically limited by the size of the matrix that can be diagonalized for larger molecules; however, relatively fewer states need to be involved than for smaller ones, in favor of the computing.
Keywords: algoritmy; Computer Simulation; furany; Furans; Spectrum Analysis; formaldehyd; počítačová simulace; Algorithms; Particle Size; Vibration; spektrální analýza; Formaldehyde; vibrace; velikost částic